Notes on credibility and economic policy - Calvo, Guillermo (1988)
‘The word "credibility" seems to spring up to the lips of policy makers with greater frequency now that several cherished simple systems (Bretton Woods, Flexible Exchange Rates, "Tablita") have run into serious implementation trouble. Sometimes one cannot even repress the suspicion that the word is no more than a stratagem to shift the blame of policy failure from those who are supposed to make policy to the innocent bystanders who are generically called "the private sector." Be it as it may, the point of the matter is that economic analysis has only recently begun to make some inroads into the credibility issue, and thus the word means different things to different people. The present notes are intended to provide an (admittedly incomplete) overview of some of the key insights of the new economics of credibility. I think that, aside from mere rhetoric, credibility plays a crucial role for economic policy, and it is, therefore, important to make the central ideas more accessible to a wider audience. The discussion will proceed through a series of steadily more realistic scenarios, culminating with a fixed-exchange rate system subject to periodic crises. We will be concerned with both the impact and the roots of imperfect credibility.